Obesitas Sebagai Faktor Utama Determinan Hipertensi pada Lansia di Puskesmas Siulak Gedang Kabupaten Kerinci - septiani, Dwi; Asparian; Eka Rini, Willia Novita (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Hypertension is one of the most common cardiovascular diseases, with a prevalence of 60.3%. In Kerinci Regency, the prevalence of hypertension in 2022 was recorded at 19.78%, while in the Siulak Gedang Health Center, there were 289 cases of hypertension. This study aims to identify the determinant factors that influence the incidence of hypertension in the elderly at the Siulak Gedang Health Center, Kerinci Regency. This study used an analytical observational design with a cross-sectional approach. A total of 101 elderly individuals aged over 60 years were selected using proportional simple random sampling. Multivariate analysis was performed using Cox regression. The results showed that the prevalence of hypertension in the elderly was 71.28%. No significant relationship was found between gender and smoking history with hypertension. However, family history, sodium consumption, and sleep quality were found to be associated with the incidence of hypertension in the elderly. The main risk factor identified was obesity, with a 14.13 times higher risk of hypertension in the elderly (p-value = 0.011). Hypertension prevention should focus on managing obesity through health education, regular check-ups, and the implementation of a healthy lifestyle to reduce the prevalence of hypertension among the elderly.